2021
DOI: 10.3390/ph14060496
|View full text |Cite
|
Sign up to set email alerts
|

Development of Non-Ethoxypropanoic Acid Type Cryptochrome Inhibitors with Circadian Molecular Clock-Enhancing Activity by Bioisosteric Replacement

Abstract: Circadian dysfunction is closely associated with an increased risk of various diseases. Considering that molecular clock machinery serves as an intrinsic time-keeping system underlying the circadian rhythm of biological processes, the modulation of the molecular clock machinery is an attractive therapeutic target with novel mechanisms of action. Based on the previous structure–activity relationship study of small molecule cryptochrome (CRY) inhibitors possessing an ethoxypropanoic acid moiety, non-ethoxypropan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…2-ethoxypropanoic acid derivatives target both CRY isoforms and inhibit their repressive function, enhancing E-box-mediated transcription. 46 , 47 Furthermore, a recent study showed that structure-based drug design could be another useful approach to find CRY1 modulators. 48 In order to obtain further insights into the mechanisms of action of these small-molecules, it is necessary to determine the crystal structures in complex with CRY proteins.…”
Section: Discussionmentioning
confidence: 99%
“…2-ethoxypropanoic acid derivatives target both CRY isoforms and inhibit their repressive function, enhancing E-box-mediated transcription. 46 , 47 Furthermore, a recent study showed that structure-based drug design could be another useful approach to find CRY1 modulators. 48 In order to obtain further insights into the mechanisms of action of these small-molecules, it is necessary to determine the crystal structures in complex with CRY proteins.…”
Section: Discussionmentioning
confidence: 99%
“…2-ethoxypropanoic acid derivatives target both CRY isoforms and inhibit their repressive function, enhancing E-box-mediated transcription. 46,47 Furthermore, a recent study showed that structure-based drug design could be another useful approach to find CRY1 modulators. 48 In order to obtain further insights into the mechanisms of action of CRY-modulating small molecules, it is necessary to determine complex crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…KS15 has anti-proliferative effects on breast cancer MCF-7 cells by increasing p53 and Bax gene expression (Chun et al, 2015). Considering that CRY1 and CRY2 have been associated with p53 suppression or degradation in other cancers (Chan et al, 2021;Jia et al, 2021) and that Cry1 and Cry2 knockout in p53 mutant mice reduces cancer risk (Ozturk et al, 2009), KS15, or its derivatives (Jeong et al, 2021) may be efficacious in the treatment of several cancers, in addition to MCF-7 breast cancer. Together, these results identified CRYs as promising targets of small-molecule compounds.…”
Section: Identification Of Cry-targeting Compoundsmentioning
confidence: 99%